City Сentres in the Paris Metropolitan Area - Horn, Christian (project baikal, 2018)
The concentration of the worldwide economic, financial and political activities in a few international metropolitan areas seems to continue. Cities that manage to be part of these networks experience generally an economic growth. But cities that fall out of these connections struggle to stay attractive for investments, jobs and people. This applies especially to medium and small size cities without a particular historic, economic or natural environment, that let them stand out. But also inside international metropolitan areas the advantages of being part of the worldwide network are not distributed equally. The metropolitan centre becomes more attractive and at the same time financially inaccessible for the majority of the population. While the high-income population stays, the low-income population is pushed out in the peripheral cities. These cities risk to concentrate an economic and social fragile population, without possessing the necessary financial means to support these households. A metropolitan and even national adjustment between the cities and territories becomes necessary. The following text describes the situation of three cities in the Paris metropolitan area.
Keywords: Paris; Juvisy-sur-Orge; Courbevoie; Ivry-sur-Seine; metropolisation; city centre; revitalisation